Implementasi Pasal 34 Ayat 1 UUD 1945 Tentang Perlindungan Anak Terlantar di Dinas Sosial Kabupaten Jember - Hoirun Nisah; Hamam Hamam (Rechtenstudent, 2021)
In recent years, the attention of the government and the public on children's lives has increased. The growth and development of community organizations engaged in child protection is one of the evidences of the high level of humanitarian feelings that exist in society. But behind it all, the concern of the government and the community is not in accordance with the current situation where more and more children are being neglected, hunting for minors, violence against children and so on. Looking at the existing laws, the realization of Article 34 paragraph 1 of the 1945 Constitution has not been maximally implemented, it is necessary to carry out serious research on the implementation of Article 34 Paragraph 1 of the 1945 Constitution. Abandoned Children Are Cared for by the State at the Social Service of Jember Regency. The focus of this research is 1) How is the implementation of the 1945 Constitution article 34 paragraph 1 of neglected children in Jember district? While the purpose of this study is to determine the implementation of the 1945 Constitution article 34 paragraph 1 of neglected children in Jember district & to find out the legal protection of neglected children in Jember, where Jember as a district cares about human rights. The approach used in this research is a qualitative approach, qualitative research methods are often referred to as naturalistic research methods, because the research is carried out in natural conditions. The type of research is a case study, where a case study is a contemporary empirical investigation in a context that is not so clear. The case study design was chosen to help researchers determine the implementation of legal protection for neglected children in Jember Regency.